Circulatory contributors to the phenotype in hereditary hemorrhagic telangiectasia - Shovlin, Claire L. (Frontiers in Genetics, 2015)
Hereditary hemorrhagic telangiectasia (HHT) is mechanistically and therapeutically challenging, not only because of the molecular and cellular perturbations that generate vascular abnormalities, but also the modifications to circulatory physiology that result, and are likely to exacerbate vascular injury. First, most HHT patients have visceral arteriovenous malformations (AVMs). Significant visceral AVMs reduce the systemic vascular resistance: supra-normal cardiac outputs are required to maintain arterial blood pressure, and may result in significant pulmonary venous hypertension. Secondly, bleeding from nasal and gastrointestinal telangiectasia leads to iron losses of such magnitude that in most cases, diet is insufficient to meet the ‘hemorrhage adjusted iron requirement.’ Resultant iron deficiency restricts erythropoiesis, leading to anemia and further increases in cardiac output. Low iron levels are also associated with venous and arterial thromboses, elevated Factor VIII, and increased platelet aggregation to circulating 5HT (serotonin). Third, recent data highlight that reduced oxygenation of blood due to pulmonary AVMs results in a graded erythrocytotic response to maintain arterial oxygen content, and higher stroke volumes and/or heart rates to maintain oxygen delivery. Finally, HHT-independent factors such as diet, pregnancy, sepsis and other intercurrent illnesses also influence vascular structures, hemorrhage, and iron handling in HHT patients. These considerations emphasize the complexity of mechanisms that impact on vascular structures in HHT, and also offer opportunities for targeted therapeutic approaches.